The hidden side of consultancy work in developing countries (1993)
Consultancy work is quite diferent in the third world that in industrialized countries. To succed, a consultant must analyse the country's economic, social and cultural aspects to assess its strengths and wealcnesses. In analyzing the context and interests in recruiting consultants, the following characteristics stand out: "administrative fear", "Curiosity", "show-off effect" and "the real need". Finally a profile description of national and foreign consultants is given, and a semiotic vision of consultancy activities is proposed.